Synergistic effect of endurance training and nettle leaf extract on the IDO1-KYN-AHR pathway homeostasis and inhibiting of liver toxicity in rats with STZ-induced diabetes - Haghshenas, Rouhollah; Aftabi, Younes; Doaei, Saied; Gholamalizadeh, Maryam (Frontiers in Endocrinology, 2023)
Introduction Diabetes adversely affects a number of hepatic molecular pathways, including the kynurenine (KYN) pathway. KYN is produced by indoleamine 2,3-dioxygenase (IDO) and activates the aryl hydrocarbon receptor (AHR). This study evaluated the effect of endurance training (EndTr) and nettle leaf extract (NLE) on the IDO1-KYN-AHR pathway in the livers of rats with streptozotocin-induced diabetes. Methods We divided 48 rats into six groups: controls (Ct), treated with EndTr (EndTr), diabetes-induced (D), D treated with NLE (D + NLE), D treated with EndTr (D + EnTr), and D treated with EndTr and NLE (D + EndTr + NLE). EndTr, D + EnTr, and D + EndTr + NLE groups were subjected to training with running on treadmill for 8 weeks, 5 days per week, 25 min in first session to 59 min at last session with intensity of 55% to 65% VO2max. Using real-time PCR gene (Ahr, Cyp1a1, and Ido1) expressions and ELISA, malondialdehyde (MDA) and protein (IDO1, AHR, and CYP1A1) levels were determined in the liver samples. Results A significant three-way interaction of exercise, nettle, and diabetes was observed on the all variables (P< 0.001). In particular, significant increases in blood glucose level (BGL), in gene and protein expression, and in MDA and KYN levels were observed in the liver samples of the D group versus the Ct group (P< 0.05). BGL and liver MDA levels were significantly lower in the D + EndTr and D + NLE groups than that in the D group. However, the D + EndTr + NLE group showed a more significant decrease in these factors (P< 0.05). In addition, liver KYN levels were significantly lower in the EndTr group compared with that in the Ct group as well as in the D + EndTr + NLE and D + EndTr groups compared with that in the D groups (P< 0.05). Whereas both the EndTr and D + NLE groups showed lower Ahr expression and AHR level compared with the Ct and D groups, respectively (P< 0.05), the D + EndTr + NLE group showed a higher significant reduction in the AHR level than the D group (P< 0.05). The Cyp1a1 expression and IDO1 level significantly decreased only in the D + EndTr + NLE group compared to that in the D group (P< 0.05). Conclusion Overall, this study showed that the combination of EndTr and NLE may synergistically restore the imbalanced IDO1-KYN-AHR pathway in diabetic liver.